2019
DOI: 10.1111/camh.12336
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty and anxiety as explanatory frameworks for extreme demand avoidance in children and adolescents

Abstract: BackgroundPathological demand avoidance (PDA) is a proposed subtype of autism spectrum disorder (ASD), characterised by extreme avoidance of demands. Demand avoidant behaviour has been proposed to be driven by an anxious need to be in control, although has never been explicitly studied. Emerging evidence suggests intolerance of uncertainty (IU) and anxiety may explain the behaviours seen in ASD. We propose these concepts may be useful starting points for furthering understanding of PDA.MethodsIn Study 1, quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…According to their parents, the AUT-PDA group displayed more behaviour that challenges during their most difficult term at school than autistic children without a PDA diagnosis (irrespective of their levels of EDA behaviours). Stuart et al (2020) identified behaviour that challenges such as aggression, as a 'last resort' behavioural response to uncertainty. It is possible that autistic children with an additional PDA diagnosis are responding with aggression when other attempts to reduce uncertainty and control their environment have failed.…”
Section: Discussionmentioning
confidence: 99%
“…According to their parents, the AUT-PDA group displayed more behaviour that challenges during their most difficult term at school than autistic children without a PDA diagnosis (irrespective of their levels of EDA behaviours). Stuart et al (2020) identified behaviour that challenges such as aggression, as a 'last resort' behavioural response to uncertainty. It is possible that autistic children with an additional PDA diagnosis are responding with aggression when other attempts to reduce uncertainty and control their environment have failed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, children with ASD score significantly higher on intolerance of uncertainty than typically developing children (Boulter et al 2014 ; Vasa et al 2018 ). This is one reason why this factor has been put forward as an important cognitive mechanism behind the anxiety symptoms and in its wake pathological demand avoidance (i.e., the obsessional avoidance of the demands of everyday life; Newson et al 2003 ) of children with this neurodevelopmental disorder (Maisel et al 2016 ; Stuart et al 2020 ).…”
Section: Rrbis and The Severity Of Social Problemsmentioning
confidence: 99%
“…"Pathological demand avoidance" (PDA) was coined in the 1980s to describe a profile seen in some children on the autism spectrum/with autistic features characterized by obsessive resistance to everyday requests, plus strategic or "socially manipulative" behavior to avoid (Newson, 1983;Newson et al, 2003). Routine requests triggered attempts to distract, elaborate excuses, negotiation, or withdrawal, which could escalate into threats, aggression, destructive behavior, or self-harm if pursued (Eaton & Weaver, 2020;Newson et al, 2003;O'Nions et al, 2018a, b;Stuart et al, 2019). Newson et al (2003) argued that these behaviors did not reflect willful defiance, and suggested that the extreme response to demands was best construed as a panic attack.…”
mentioning
confidence: 99%
“…It has been argued that PDA should be viewed as a collection of symptoms rather than a syndrome (Green et al, 2018). However, there is emerging consensus that some children with ASD do present with a behavioral profile resembling PDA, evidenced by work from several independent groups (Eaton & Banting, 2013;Eaton & Weaver, 2020;Gillberg et al, 2015;Green et al, 2018;O'Nions et al, 2018a, b;Stuart et al, 2019), and international scholars who report that some children with ASD find routine demands aversive and may react to pressure to comply with avoidance and behavior that challenges (e.g., Agazzi et al, 2013;Lucyshyn et al, 2004Lucyshyn et al, , 2007.…”
mentioning
confidence: 99%